Randomized, Double-blind, Placebo-controlled Clinical Trial for the Evaluation of the Efficacy and Safety of Artemisia and Green Tea Extract SD1003F in Volunteers with Helicobacter pylori-associated Gastric Discomfort - Sang Oh Kwon; Dong Yun Kwak; Sung Pyo Hong; Won Hee Kim; Jong Min Park; Young Min Han; You Kang; Eun A Kang; Seohyun Jo; Ki Baik Hahm (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: A previous study showed that dietary intervention with Artemisia and green tea extracts, i.e., SD1003F, relieved Helicobacter pylori-associated chronic atrophic gastritis in a mouse model. We continue the research through the current randomized double-blind clinical trial to evaluate the efficacy and safety of the intervention for H. pylori-associated gastric discomfort. Materials and Methods: Forty-nine volunteers who tested positive for H. pylori infection received either placebo or SD1003F for 10 weeks and their functional dyspepsia-related quality of life (QOL) was evaluated. H. pylori infection using a urea breath test (UBT), measurement of pepsinogen level using GastroPanel. Adverse effects with biochemical changes were also evaluated. Results: SD1003F administration significantly improved health related-QOL, including dietary intake, emotional stability, life pattern, and social factors relevant to gastric discomfort, in comparison to the control (P＜0.05). The mean UBT measurement significantly decreased in the SD1003F group (P＜0.05). In 2 of the 24 volunteers, SD1003F alone eradicated H. pylori infection, with significant improvements in endoscopic findings. GastroPanel analysis revealed significant improvements that reflect rejuvenation of gastric atrophy in the SD1003F group. No significant side effect was observed in any participant. Conclusions: SD1003F (Artemisia and green tea extract), is a potential phytochemical to improve H. pylori-associated gastric discomfort.